Ticks infesting humans in Italy and associated pathogens - Domenico Otranto; Filipe Dantas-Torres; Alessio Giannelli; Maria Stefania Latrofa; Antonio Cascio; Stefania Cazzin; Silvia Ravagnan; Fabrizio Montarsi; Sergio Aurelio Zanzani; Maria Teresa Manfredi; Gioia Capelli (Parasites & Vectors, 2014)
Abstract Background Ticks may transmit a large variety of pathogens, which cause illnesses in animals and humans, commonly referred to as to tick-borne diseases (TBDs). The incidence of human TBDs in Italy is underestimated because of poor surveillance and the scant amount of studies available. Methods Samples (n = 561) were collected from humans in four main geographical areas of Italy (i.e., northwestern, northeastern, southern Italy, and Sicily), which represent a variety of environments. After being morphologically identified, ticks were molecularly tested with selected protocols for the presence of pathogens of the genera Rickettsia, Babesia, Theileria, Candidatus Neoehrlichia mikurensis, Borrelia and Anaplasma. Results Ticks belonged to 16 species of the genera Argas, Dermacentor, Haemaphysalis, Hyalomma, Ixodes and Rhipicephalus, with Ixodes ricinus (59.5%) being the species most frequently retrieved, followed by Rhipicephalus sanguineus sensu lato (21.4%). Nymphs were the life stage most frequently retrieved (41%), followed by adult females (34.6%). The overall positivity to any pathogen detected was 18%. Detected microorganisms were Rickettsia spp. (17.0%), Anaplasma phagocytophilum (0.8%), Borrelia afzelii (0.5%), Borrelia valaisiana (0.3%), C. N. mikurensis (0.5%) and Babesia venatorum (0.6%). Conclusions Results indicate that people living in the Italian peninsula are at risk of being bitten by different tick species, which may transmit a plethora of TBD causing pathogens and that co-infections may also occur.